MENYIASATI PENYEMPITAN MUSIM TANAM PADI DENGAN BUDIDAYA RATUN DAN SALIBU - Marsid Jahari; Parlin H. Sinaga (DINAMIKA PERTANIAN, 2019)
ABSTRACT One method that can be done to save time during the growing season due to climate change is the cultivation of ratoon or Salibu. The study was conducted in Pelalawan Regency in July-October 2014 and in Kapuas Regency in December 2012-August 2013. The purpose of the study was to determine the response of rice lines in the ratoon and Salibu cultivation system in tidal land. The study was designed according to a randomized completely block design which was repeated three times. The results showed that the cultivation of salibu method in flooding tidal land did not produce grain, whereas in tidal land overflows type C that water could be regulated, lines P1D-KK-A26, P1D-KK-A48b, and P5E-KK-A5 gave yields of salibu more than 4 t ha-1 DMG. Cultivation of rice ratoon can be carried out in flooded or regulated water. Lines P1F-B-A15, P1D-KK-A26, P1D-KK-A45, P1D-KK-A48b, P1D-KK-A67, and P5E-KK-A5 can be cultivated both ratoon and salibu. Efforts to anticipate the limited growing season with the cultivation technique of ratoon can be carried out on tidal land that is dry or flooding, while the salibu technique is good carried out on land that is not always flooded.